2020
DOI: 10.3389/frsc.2020.598516
|View full text |Cite
|
Sign up to set email alerts
|

SDG Implementation at the Local Level: Lessons From Responses to the Coronavirus Crisis in Three Cities in the Global South

Abstract: A body of work is starting to emerge that seeks to build on the challenges and lessons of the current global coronavirus crisis for long term sustainability planning and development. This perspective article argues that central to such reflections should be an acknowledgment of the intense territorial impact of the crisis, especially in the places where most of the world's population is increasingly living: cities. We review existing frameworks for SDG implementation in the cities of Bengaluru (India), Medelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…A recent review of existing frameworks for SDG implementation in three cities in the global south, including Cape Town in South Africa, found the link between existing data systems and the data required to monitor and report on SDG implementation is still emerging. (15) The authors of the review suggest that local responses to COVID-19 highlight that required data systems can be put in place quickly.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of existing frameworks for SDG implementation in three cities in the global south, including Cape Town in South Africa, found the link between existing data systems and the data required to monitor and report on SDG implementation is still emerging. (15) The authors of the review suggest that local responses to COVID-19 highlight that required data systems can be put in place quickly.…”
Section: Discussionmentioning
confidence: 99%
“…China began with a decentralised approach, with negative outcomes from Wuhan province, before moving to a centralised approach, while India moved from a central responsive to a more decentralised approach, maintaining a low spread of the disease through 2020 (Kosec & Mogues, 2020). A review of decentralised decision-making in the Covid-19 response in Bengaluru (India), Medellin (Colombia) and Cape Town (South Africa) found that cities took a more decisive role in Covid-19 response than they have tended to have in development decisionmaking leading up to the pandemic (Mejia-Dugand et al, 2020). In Bengaluru and Medellin, the authors find that city-level government adopted a nearly autonomous approach to Covid-19 management, independent of national-level directive.…”
Section: Decentralised Decision-makingmentioning
confidence: 99%
“…In Cape Town, national and provincial-level directives were seen to be serving as the main policy influence. The authors also argue that local engagement has been critical in Covid-19 responses and that the partnerships that have been created throughout the crisis between different levels of decision-making can be built upon beyond the Covid-19 crisis (Mejia-Dugand et al, 2020) Reviewing the experience of decentralisation in three countries with some degree of decentralisation -Ethiopia, Kenya, South Africa -Steytler concludes that "the impact of the pandemic on decentralised governance largely depends on who are the decisionmakers" (quoted in Stevens, 2020). In South Africa, the central government played a dominant role in the country's response through a national disaster advisory body, whose imposition eventually led some to question the body's legal and constitutional status (Stevens, 2020).…”
Section: Decentralised Decision-makingmentioning
confidence: 99%
“…The majority of the world's leaders and their governments are committed to implementing the 2030 Agenda, goals, and targets [11,12]. This follow-up is intended to strengthen policies and institutions of governments for the implementation of the SDGs at the national level called Voluntary National Reviews (VNRs), and a standard and inclusive framework should be provided.…”
Section: Introductionmentioning
confidence: 99%
“…Countries like Germany, Sweden, Japan, Norway, Denmark, Finland, Belgium, and the Netherlands have already aligned SDGs with their national development strategies [18,19]. Thus, while almost all of the states involved have already presented or had intended to show their VNRs by 2021, only a handful of initiatives around the world have tried to prepare VLR at the city level [12,20]. These VLRs could be a practical approach in accelerating the progress of SDG implementation [10] and offer and contribute to addressing the common obstacles and challenges that urbanization represents.…”
Section: Introductionmentioning
confidence: 99%